How important are mutual recognition agreements for trade facilitation? - Lucian Cernat (European Centre for International Political Economy (ECIPE), 2022)
Trade in the 21st century may face lower tariffs, but regulations that affect international trade in goods and services have proliferated. While regulations are important for many public policy objectives, different and complex non-tariff measures can become unnecessarily costly trade barriers for the millions of companies engaged in international trade. Trade policy can play a crucial role in reducing these unnecessary costs, without impairing the ability of regulatory authorities to carry out their public policy responsibilities. Mutual recognition agreements (MRAs) are a concrete trade policy instrument, specifically designed to achieve this dual objective. This paper revisits the arguments in favour of upgrading the existing EU MRAs to cover 21st century regulatory aspects impacting trade flows, offering empirical evidence on the positive difference MRAs have both on the value of exports and on increasing the number of exporting firms and their product portfolio towards new export destinations. The paper also summarises the results of a recent EU firm-level survey on the importance of MRAs for export performance. The results of the EU business surveys confirm the need for a renewed attention to MRAs, in particular with regard to emerging regulatory issues.
Keywords: 330; Außenwirtschaftsförderung; Außenwirtschaftspolitik; Handelsliberalisierung; Nichttarifäre Handelshemmnisse; EU-Staaten; Welt